OX40 ligand newly expressed on bronchiolar progenitors mediates influenza infection and further exacerbates pneumonia. Issue 4 (14th March 2016) - Hirano, Taizou; Kikuchi, Toshiaki; Tode, Naoki; Santoso, Arif; Yamada, Mitsuhiro; Mitsuhashi, Yoshiya; Komatsu, Riyo; Kawabe, Takeshi; Tanimoto, Takeshi; Ishii, Naoto; Tanaka, Yuetsu; Nishimura, Hidekazu; et al.
Abstract: Influenza virus epidemics potentially cause pneumonia, which is responsible for much of the mortality due to the excessive immune responses. The role of costimulatory OX40–OX40 ligand (OX40L) interactions has been explored in the non‐infectious pathology of influenza pneumonia. Here, we describe a critical contribution of OX40L to infectious pathology, with OX40L deficiency, but not OX40 deficiency, resulting in decreased susceptibility to influenza viral infection. Upon infection, bronchiolar progenitors increase in number for repairing the influenza‐damaged epithelia. The OX40L expression is induced on the progenitors for the antiviral immunity during the infectious process. However, these defense‐like host responses lead to more extensive infection owing to the induced OX40L with α‐2, 6 sialic acid modification, which augments the interaction with the viral hemagglutinin. In fact, the specific antibody against the sialylated site of OX40L exhibited therapeutic potency in mitigating the OX40L‐mediated susceptibility to influenza. Our data illustrate that the influenza‐induced expression of OX40L on bronchiolar progenitors has pathogenic value to develop a novel therapeutic approach against influenza. Synopsis: OX40 ligand (OX40L) is a costimulatory molecule known to be expressed preferentially on antigen‐presenting cells for T‐cell priming. Here, an unprecedented mechanism is found by which OX40L exacerbates influenza pneumonia on bronchiolar progenitors by functioning as the virus receptor. In lower respiratory infection with influenza virus, the number of bronchiolar progenitors is increased for repair of damaged epithelial cells. The OX40L expression is enhanced on the influenza‐expanded bronchiolar progenitors to bolster the host immune response. The infection is paradoxically worsen by accelerated viral binding to the bronchiolar progenitors via the α‐2, 6 sialic acid of glycosylated OX40L protein. Abstract : OX40 ligand (OX40L) is a costimulatory molecule known to be expressed preferentially on antigen‐presenting cells for T‐cell priming. Here, an unprecedented mechanism is found by which OX40L exacerbates influenza pneumonia on bronchiolar progenitors by functioning as the virus receptor.